(untitled) (Sir Salimullah Medical College Journal, 2026)
Nintedanib is an oral tyrosine kinase inhibitor targeting VEGF, PDGF, and FGF receptors and is approved for idiopathic pulmonary fibrosis and other fibrosing interstitial lung diseases. Gastrointestinal adverse events are common, but severe upper gastrointestinal bleeding and gastric antral vascular ectasia (GAVE) are rarely described. A 76 year old woman with fibrosing interstitial lung disease, treated with nintedanib 150 mg twice daily for over two years, presented with melena, dyspnea, edema, and profound anemia (hemoglobin 4.0 g/dL). Endoscopy revealed classic GAVE, successfully treated with argon plasma coagulation. Extensive evaluation excluded cirrhosis, systemic sclerosis, malignancy, peptic ulcer disease, and other secondary causes of GAVE. Nintedanib was discontinued, after which melena resolved and hemoglobin stabilized without recurrence of bleeding. Given nintedanib’s anti VEGF and anti PDGF effects and prior case reports of GAVE under nintedanib and other TKIs, a probable causal association was considered. This case highlights GAVE as a rare but potentially life threatening and under recognized complication of long term nintedanib therapy and underscores the need for vigilance and early endoscopic evaluation in antifibrotic treated patients presenting with unexplained anemia or upper GI bleeding. Sir Salimullah Med Coll J 2025; 33: 70-72